IMPROVING MONITORING OF HISTORICAL SITES BASED ON GEOINFORMATION TECHNOLOGIES (USING THE EXAMPLE OF UZBEKISTAN) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article broadly and in detail discusses the issues of using geoinformation technologies in the protection, continuous monitoring and management of historically significant lands in the Republic of Uzbekistan. The study is based on the analysis of regulatory legal acts of the Republic of Uzbekistan in the field of land and cultural heritage, as well as local scientific literature. It is substantiated that the capabilities of geoinformation technologies for remote sensing, digital cartography, spatial analysis and monitoring are effective scientific and practical tools for monitoring historically significant territories.